REMARKABLE CORRELATION OF NON-GENETIC FACTORS WITH GROWTH TRAITS IN TWO BREEDS OF SHEEP - Aljubouri, T. R. S.; Hassan, A. F.; Al-Shuhaib, M. B. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted at the college of agriculture – Al-Qasim Green University to investigate the effect of breed and age of dams on several growth traits of two sheep breeds, including 123 Iraqi Awassi and 78 Iranian Karakul breeds. Variables growth traits were examined in the present study, namely body weight (BW), body length (BL), wither height (WH), rump height (RH), and chest circumference (CC), and abdominal circumference (AC). Results indicated the absence of a significant effect between both breeds in all investigated growth traits in birth. Meanwhile, a significant (P